An inquiry into the regional unemployment disparities in Tunisia: a spatial Durbin model. Issue 2 (3rd July 2021) - Jeguirim, Khaled
ABSTRACT: This study uses a spatial Durbin model in identifying possible causes of the overdispersion into regional unemployment in Tunisia. Data properties were identified using exploratory spatial data analysis which indicates significant neighbouring effects for several variables. Differences in socio-economic structure between regions explain in part these phenomena. Education is a key factor and also some constraints prevent married women from taking up jobs, thus exacerbating regional unemployment. Regions with important tourism activity do well than others. Tourism sector exhibit important spillover effects on regional unemployment while the impact of agricultural activity is confined to local labour market. The diversification of the industrial fabric at a regional level is not a sine qua non for differences reduction in regional unemployment rates. Developing road infrastructure helps to reduce unemployment disparities.